Log9(x+1)-log9(x-2)=log9(x+13)-1 надо

yanachor25 yanachor25    3   25.08.2019 22:50    1

Ответы
niganai niganai  05.10.2020 19:46
Log9(x+1)-log9(x-2)=log9(x+13)-1  ОДЗ х+1>0  x>-1
                                                                 х-2       x>2
                                                                 х+13    x>-13
Log₉(x+1)-log₉(x-2)=log₉(x+13)- log₉9

log₉(x+1) /(x-2) =log₉(x+13)/ 9

(x+1) /(x-2)=(x+13)/ 9

9*(x+1)=(x+13)*(x-2)

9x+9 =x²+13x-2x-26

x²+2x-35=0

D=4+140=144 √D=12

x₁=(-2+12)/2=5

x₂=(-2-12)/2=-7 не подходит под ОДЗ 
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра